Multi-Tasking and Making a Living from Music: Investigating Music Careers in the Independent Music Scene of Milan. (June 2018) - Tarassi, Silvia
The analysis of popular music scenes has traditionally focused upon grass-roots music-making practices, without considering how these practices are rooted in the organizational and economic dynamics that characterize today's cultural economy. This article suggests the need to look at music production in music scenes as a more professionalized activity which requires entrepreneurial skills and economic sustainability. Drawing on the findings of a six-month fieldwork study of the music scene of Milan, this article will attempt to re-conceptualize our understanding of music scenes and to explain how the desire to make a living through music requires the members of a scene to be engaged to a significant degree in multi-tasking and multi-jobbing, which allows them to survive in a risky, precarious environment.